Ghana : transition to democracy - Ninsin, Kwame Akon, 1938-; Codesria (Dakar, Senegal : Codesria, 1998)
Appendix 1 : Profile of political parties, 1946-1994. - 2 : Government Ghana 1957-1994. - 3 : A chronology of major political events since 31 December 1981. - 4 : Other forms of direct foreign assistance.
Structural adjustment programme and the transition to democracy / Charles D. Jebuni and Abena D. Oduro -- Civic associations and the transition to democracy / Kwame A. Ninsin -- Political parties and the transition to multi-party politics in Ghana / Kwesi Jonah -- State organisations in the transition to constitutional democracy / Gilbert Keith Bluwey -- Transtition to democracy and control over Ghana's military and security establishments / Robin Luckham -- International community and Ghana's transition to democracy / Kwame Boafo-Arthur -- Press and the transition to multi-party democracy in Ghana / Kwame Karikari -- Postscript : elections, democracy and elite consensus / Kwame A. Ninsin.
Includes bibliographical references (pages 241-252).
Keywords: Democratization -- Ghana; Politics and government; Aufsatzsammlung